Answer:
b. 3 times
Step-by-step explanation:
Lets take
Coefficient for ordinary glass = α₁
Coefficient for pyrex glass = α₂
Given that α₁ = 3 α₂
Initial length of both glasses are equal = L
Change in the temperature is also same .= ΔT
We know that change in the length given as
ΔL = L α ΔT
Therefore
![(\Delta L_1)/(\Delta L_2)=(L\alpha_1\Delta T)/(L\alpha_2\Delta T)](https://img.qammunity.org/2020/formulas/physics/college/ij8z1nlspqhh628pqwllk289u35j63tmi1.png)
![(\Delta L_1)/(\Delta L_2)=(3\alpha_2)/(\alpha_2)](https://img.qammunity.org/2020/formulas/physics/college/2u9cktkskytqrks3rv66zcbaec4zq37pw1.png)
ΔL₁ = 3ΔL₂
Therefore change in the length of original glass is three time of pyrex glass.
b. 3 times